Pengembangan Media Ular Tangga Berbasis Kearifan Lokal untuk Meningkatkan Pengenalan Konsep Bilangan 1-20 dan Motorik Kasar Anak TK Negeri Pembina Kecamatan Pecalungan Kabupaten Batang - Suryanti, Suryanti; Ngatmini, Ngatmini; Sumarno, Sumarno (Universitas PGRI Semarang, 2025)
Education of children aged 5-6 years is a critical foundation for children's cognitive and motor development, but the ability to recognize numbers 1-20 and gross motor skills of children in Pembina State Kindergarten, Pecalungan District is still low. This is triggered by monotonous conventional learning methods, the lack of innovative media, and the lack of integration of local wisdom values. This study developed a snake and ladder game media based on local wisdom to overcome these problems while preserving regional culture. The purpose of the study was to test the feasibility, effectiveness, and practicality of the media in improving the ability to recognize numbers and gross motor skills of children aged 5-6 years. The research method used the Research and Development (RD) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, involving 20 group B students as subjects. The research instruments included validation sheets of material and media experts, teacher-student response questionnaires, cognitive tests, and gross motor observation rubrics. Data analysis was carried out using descriptive statistics, normality tests, t-tests, and N-Gain calculations. The validation results showed that the media was considered very feasible by material experts (87.5%) and media experts (85%). The t-test proved a significant increase in post-test scores (average 80) compared to pre-test (55) with N-Gain 0.6 (moderate category). Gross motor skills increased, namely 70% of students reached the category of Developing According to Expectations (BSH) and 30% Developing Very Well (BSB). The practicality of the media reached 93.33% based on teacher assessment. The conclusion of the study confirmed that local wisdom-based snakes and ladders media is effective in improving academic and motor skills, while strengthening children's cultural identity. The implication is that this media is recommended as an alternative for interactive culture-based learning in children aged 5-6 years.